PENGARUH MODEL COOPERATIVE LEARNING TIPE JIGSAW TERHADAP EMPATI KOMUNIKATIF DALAM PEMBELAJARAN IPS SISWA KELAS V SEKOLAH DASAR KELURAHAN SUNTER JAYA - Riska Azzahra; Taofik; Nidya Chandra Muji Utami (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of the Jigsaw Cooperative Learning model on communicative empathy in the learning of fifth-grade elementary school students in Sunter Jaya Village. This study uses a quasi-experimental method with a Nonequivalent Control Group Design. The sample used in this study consisted of two classes selected using the simple random sampling technique, namely class VC as the experimental class and class VB as the control class. The data collection technique used was a Likert scale questionnaire with four indicators of communicative empathy: the ability to convey ideas effectively, the ability to listen actively, the ability to convey information clearly, and the use of polite and effective language. Based on the results of the Independent Sample T-Test hypothesis test, a significance value of < 0.001 was obtained, which is less than 0.05. Therefore, it can be said that H0 is rejected and Ha is accepted. These findings indicate that the Jigsaw Cooperative Learning model is more effective than the question answer model in improving students' communicative empathy. Therefore, the Jigsaw Cooperative Learning model is recommended as an alternative social studies learning model that is not only academically oriented but also focuses on character building and social skills development.